1993
DOI: 10.1103/physrevlett.71.2851
|View full text |Cite
|
Sign up to set email alerts
|

Collision of two black holes

Abstract: We study the head-on collision of two equal mass, nonrotating black holes. We consider a range of cases from holes surrounded by a common horizon to holes initially separated by about 20M , where M is the mass of each hole. We determine the waveforms and energies radiated for both the ℓ = 2 and ℓ = 4 waves resulting from the collision. In all cases studied the normal modes of the final black hole dominate the spectrum. We also estimate analytically the total gravitational radiation emitted, taking into account… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
267
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(288 citation statements)
references
References 12 publications
(10 reference statements)
20
267
0
1
Order By: Relevance
“…on a 3-dimensional spacelike hypersurface) and are then stepped to the next instant using an "ADM" [2] form of the Einstein evolution equations [3]. The evolution is unconstrained, and maintenance of the constraint functions with small error is verified throughout the run.This work extends previous work on headon encounters [4][5][6][7]. It is comparable to recent results of Brügmann [8]: non-headon black hole evolution through to significant interaction and merger.…”
supporting
confidence: 80%
“…on a 3-dimensional spacelike hypersurface) and are then stepped to the next instant using an "ADM" [2] form of the Einstein evolution equations [3]. The evolution is unconstrained, and maintenance of the constraint functions with small error is verified throughout the run.This work extends previous work on headon encounters [4][5][6][7]. It is comparable to recent results of Brügmann [8]: non-headon black hole evolution through to significant interaction and merger.…”
supporting
confidence: 80%
“…For instance, consider the good agreement between numerical relativity simulations of equal-mass BH collisions and the point-particle extrapolations to equal-mass systems. In D = 4, early work [42] and more recent simulations (see e.g. [21]) found that the TABLE I.…”
Section: Resultsmentioning
confidence: 99%
“…For example, if the black hole is small, we expect to find in the gravitational radiation spectra a strong peak located at ω 2 = 4n 2 + l(l + 1) , n = 1, 2, ... [5]. Moreover, some major results in perturbation theory and numerical relativity [27,28], studying the collision of two black holes, with masses of the same order of magnitude, allow us to infer that evolving the collision of two black holes in AdS spacetime, should not bring major differences in relation to our results (though it is of course a much more difficult task, even in perturbation theory). In particular, in the small black hole regime, the spectra and waveforms should be dominated by quasinormal ringing.…”
Section: Discussionmentioning
confidence: 99%